Hot cracking, crystal orientation and compressive strength of an equimolar CoCrFeMnNi high-entropy alloy printed by selective laser melting. (July 2020) - Niu, Pengda; Li, Ruidi; Zhu, Shuya; Wang, Minbo; Chen, Chao; Yuan, Tiechui
Highlights: The crystalline texture highly depends on VED. The average grain size gradually increased with the increase of VED. The preferred orientation of printed sample follows the transition 〈2 3 3〉→〈0 0 1〉→〈2 0 3〉→〈1 0 1〉 with the increase of VED. Abstract: Hot cracking, grains size, crystal orientation and compressive strength of an equimolar CoCrFeMnNi high-entropy alloy (HEA) printed by selective laser melting (SLM) were investigated. The CoCrFeMnNi HEA printed by SLM suffered from hot cracking no matter of the employed printing parameters. The preferred orientation of the printed sample was transformed in the order: 〈2 3 3〉→〈0 0 1〉→〈2 0 3〉→〈1 0 1〉, as the volumetric energy density (VED) rises. Also, the increased VED favors the grain growth and the increase of the grain orientation spread, owing to the presence of high temperature gradient and larger residual stress. The fracture strength increases with the VED, and the maximum compressive strength rises to 2447.7 MPa, but the elongation rate is still 77.6% due to the ultrafine microstructure. The results of this study have reference value for the preparation of HEA materials with controllable grain characteristics, crystalline texture and complex structures by SLM.